Avaliação da adição de lodo gerado no tratamento de efluentes frigoríficos (LF) como matéria-prima na fabricação de argila expandida - Machado Júnior, Antônio Célio (Universidade do Vale do Rio dos Sinos, 2019)
The growing demand for more sustainable systems contributes to studies that involve waste management. Legislation already requires industries to take responsibility for waste generated. In Brazil, a residue generated in large volumes and that worries about its final destination, is the poultry industry sludge (PS). It is a result of the effluent treatment process used in most of the country's refrigerators. Therefore, it is suggested to identify its characteristics to predict possibilities of transformation of the residue into raw material in other processes. One sector that stands out in the possibility of absorbing waste is the construction sector, given its dependence on natural resources and diverse use throughout its chain. The literature indicates tendencies of recovery of the residue in the manufacture of light aggregates such as expanded clay. In this sense, this research had as main objective to evaluate the manufacture of expanded clay with addition of PS. For this, PS was collected from an industry and natural clay from two deposits of the same region, thus identifying the possibility of industrial symbiosis between the two companies. Then the raw materials were characterized in physical, chemical, mineralogical and thermal form. Finally, sintering tests were carried out with the incorporation of 0%, 5% and 10% by mass of PS in a clayey matrix. The heat treatment was performed at temperatures of 1100ºC, 1150ºC and 1200ºC. Among the results, it was verified that the clays have major compounds of SiO2, Al2O3 and Fe2O3, while the PS presented 94.79% of organic matter. The clays presented crystalline phases of quartz and montmorillonite in common, while clay 1 also presented hydrated calcium and manganese oxide and clay 2 presented aluminum and potassium silicate. The potential for the production of expanded clay was foundin one of the clays of the region, where there was an expansion of 29.10% in volume, at a temperature of 1200ºC. Already with the addition of PS in the clay, there was an expansion of 6.42% in the 5% PS content at the same temperature. Through the XRD the mineralogical phases of quartz, hematite, silimanite and muscovite in the obtained materials were verified. For the specimens that underwent pyroplastic expansion, the absorption tests were of 7.83% for referent clay and 6.62% for clay with 5% of PS. The apparent specific mass of the expanded clay was 1.22g/cm³ and 1.39g/cm³, respectively. The morphology analysis showed vitrified outer layer and porous inner layer, typical characteristics of expanded clay. Considering an overview of the results, in the conditions performed in this research, the LF was not efficient in the process of production of light aggregates, because its addition caused the inhibition of the clay expansion.
Keywords: Valorização de resíduos; Lodo de frigorífico; Argila expandida; Reciclagem; Waste recovery; Poultry industry sludge; Expanded clay; Recycling; ACCNPQ::Engenharias::Engenharia Civil